New-born screening of metabolites with liquid chromatography-mass spectrometry and gas chromatography–mass spectrometry: a metabolic and molecular signatures methyl malonic aciduria with combined oxidative phosphorylation deficiency-10: a rare case report - Subramaniam, Samu; A. T., Arasar Seeralar; Subramaniam, Shyama; Chelladurai, Subhasree Ramarathinam (International Journal of Contemporary Pediatrics, 2023)
An uncommon autosomal recessive organic acid disease is malonic aciduria. This disease may be easily identified and included in the NBS programmes by means of the widespread use of tandem mass spectrometry’s in the study of the amino acid/acylcarnitine profile using dried blood spots (DBS) for newborn screening. In Tamil Nadu, we reported the first screened and diagnosed with malonic aciduria by newborn screening (NBS) in early neonatal period. The patient possesses a malonyl-CoA decarboxylase genetic variation not previously described. This disease should be distinguished from a related malonic and methylmalonic aciduria problem. Malonic aciduria’s clinical phenomenology varies and pathogenesis is not completely known. The proper treatment regimen, nutritional therapy or frequent follow-up to these individuals are not guided or recommended. The majority of current treatment data is based on a single research or case report.